Nd3+ doped BaSnF4 solid electrolyte for advanced room-temperature solid-state fluoride ion batteries. Issue 12 (15th August 2020) - Liu, Lei; Yang, Li; Shao, Dingsheng; Luo, Kaili; Zou, Changfei; Luo, Zhigao; Wang, Xianyou
Abstract: The successful application of BaSnF4 solid electrolyte in room-temperature (RT) solid-state fluoride ion batteries (FIBs) marks an innovative stage in the research of FIBs, although its ionic conductivity faces still many challenges. To promote the ionic conductivity of BaSnF4 solid electrolyte for advanced RT solid-state FIBs, herein BaSnF4 doped with different stoichiometric ratios Nd 3+ through wet chemical method is prepared and used as the solid electrolyte of solid-state FIBs. The morphology and structure of Ba1-x Ndx SnF4+x (0≤x≤0.08) solid solutions are investigated with X-ray diffraction (XRD) and scanning electron microscopy (SEM). Particularly, ionic transport properties of Ba1-x Ndx SnF4+x solid solutions have been investigated via electrochemical impedance spectroscopy (EIS) and chronoamperometry measurements. The results indicate that the RT ionic conductivity of Ba0.98 Nd0.02 SnF4.02 pellet sintered at 300 °C for 2 h is as high as 5.8 × 10 −4  S cm -1, which is nearly 3 times larger than un-doped BaSnF4 sample. The solid-state FIB cells, in which Ba0.98 Nd0.02 SnF4.02 is used as the solid electrolyte, Sn as anode and BiF3 as the cathode, exhibit the discharge specific capacities of 135 and 95 mAh g -1 on the 1 st and 20 th cycles, respectively. Besides, the rate performance of Sn/Ba0.98 Nd0.02 SnF4.02 /BiF3 battery ranges from 12.7 to 127 μA cm -2 is also obtained for the first time. The successful application of Nd 3+ doped BaSnF4 solid electrolyte in RT solid-state FIBs provides a new route for the research of solid electrolyte and FIBs.